THE EFFECTIVENESS OF PICTURES IN ENHANCE WRITING SKILL OF ELEVENTH GRADE SENIOR HIGH SCHOOL STUDENTS IN SMK BINA NUSANTARA SOUTH LAMPUNG (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this research was to find the effectiveness of pictures in writing class of senior high school students. This research was used quantitative method with using the quasi-experimental design. The subject of the research was the second year students of on senior high school in Marga Agung Regency, South Lampung, Lampung, Indonesia. The total number of population is 42 students which are distributed in 2 classes. Each class consists of 21 students. The sampling technique used in this research is cluster random sampling. A writing test was used as the instrument to gather information on the students' writing proficiency using the images. The researcher came to the conclusion that the images improve senior high school pupils' writing abilities based on the results.